Growth behaviour of maize under different crop establishment methods and nitrogen levels - Raihan, Obaidullah; Kaur, Ramanjit; Shivay, Y.S.; Dass, Anchal; Bari, Shah Mahmood (Annals of Agricultural Research, 2018)
A field experiment was conducted during (Kharif, April-August) season of 2015 at ANASTU, Afghanistan National Agricultural Sciences and Technology University, Kandahar, to study the effect of crop establishment methods and N levels on maize growth and productivity in semi-arid region of Afghanistan. The experiment consists of 12 treatment combinations i.e. three crop establishment methods; broadcast method, line sowing and ridge sowing method in main plot and four N levels; 0, 120, 160, 200 kg N/ha in sub-plots. Maize variety CS-200 was sown using a seed rate of 25 kg/ha. Results of this study indicated that that crop establishment methods had a significant effect on growth parameters like plant height, dry mater accumulation and crop growth rate and relatively higher plant height (180.5 cm), dry matter accumulation (243.8 g/plant), crop growth rate (2.28 g/plant/day) were recorded in ridge planting method. In case of N levels, maximum plant height (183.7 cm), leaf area index (3.87), dry matter accumulation (244.1 g/plant) and crop growth rate (2.5 g/plant/day) were recorded where 200 kg N/ha was applied.